Berberine inhibited metastasis through miR-145/MMP16 axis in vitro - Jie Li; Songlin Zhang; Lei Wu; Meili Pei; Yu Jiang (BMC, 2021)
Abstract Ovarian cancer is the first leading cause of death in gynecological cancers. The continuous survival and metastasis of cancer cells are the main causes of death and poor prognosis in patients with ovarian cancer. Berberine is an effective component extracted from the rhizomes of coptis chinensis and phellodendron chinensis. In our study, we aim to explore the molecular mechanism underlying the regulation of proliferation, migration and invasion by berberine in ovarian cancer cells. CCK8 assay was used for detection of proliferative capacity of SKOV3 and 3AO cells. Wound healing assay was used to estimate cell migration and transwell assay was used to assess cell invasion. The mRNA expression of miR-145 and MMP16 were examined by quantitative real-time polymerase chain reaction (qRT-PCR). The protein level of MMP16 was detected by western blot analysis. In addition, luciferase reporter assays were used to demonstrate MMP16 was a target of miR-145. The results demonstrated berberine inhibited proliferation, migration and invasion, promoted miR-145 expression, and decreased MMP16 expression in SKOV3 and 3AO cells. MMP16 was a target of miR-145. Moreover, downregulation of MMP16 contributed to the inhibition of proliferation, migration and invasion by berberine. Together, our results revealed that berberine inhibited proliferation, migration and invasion through miR-145/MMP16 in SKOV3 and 3AO cells, highlighting the potentiality of berberine to be used as a therapeutic agent for ovarian cancer.